Identification of a bilirubin receptor that may mediate a component of cholestatic itch - Meixiong, James (eLife, 2019)
Various pathologic conditions result in jaundice, a yellowing of the skin due to a buildup of bilirubin. Patients with jaundice commonly report experiencing an intense non-histaminergic itch. Despite this association, the pruritogenic capacity of bilirubin itself has not been described, and no bilirubin receptor has been identified. Here, we demonstrate that pathophysiologic levels of bilirubin excite peripheral itch sensory neurons and elicit pruritus through MRGPRs, a family of G-protein coupled receptors expressed in primary sensory neurons. Bilirubin binds and activates two MRGPRs, mouse MRGPRA1 and human MRGPRX4. In two mouse models of pathologic hyperbilirubinemia, we show that genetic deletion of either Mrgpra1 or Blvra, the gene that encodes the bilirubin-producing enzyme biliverdin reductase, attenuates itch. Similarly, plasma isolated from hyperbilirubinemic patients evoked itch in wild-type animals but not Mrgpra1(-/-) animals. Removing bilirubin decreased the pruritogenic capacity of patient plasma. Based on these data, targeting MRGPRs is a promising strategy for alleviating jaundice-associated itch.